Indeks Kepuasan Pasien BPJS Kesehatan Terhadap Pelayanan Rumah Sakit Mata Masyarakat Jawa Timur - Alya Hazfiarini; Ernawaty Ernawaty (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2016)
Quality control is an essential part in delivering health services, especially under the implementation of national health insurance nowsdays. Particularly for health facilities, it is a crucial to control its services quality as it is a requirment in establishing a partnership with BPJS Kesehatan. Community Eye Hospital East Jawa has been worked with BPJS Kesehatan for years. The number of BPJS Kesehatan patients was more than 50% from total number of patients on August 2015 – January 2016. The aims of this study is to analyse the satisfation of BPJS Kesehatan patients towards the services of the hospital using 14 indicators which adopted from Kepmenpan No. Kep/25/M.PAN/2/2004. The study applied observational analysis with cross sectional design and accidental sampling. The overall indicators measurements pointed out that the quality of services of the hospital falled into excellent category (Satisfaction index / IKM = 82,32). However, there are 5 of 14 indicators, namely, speed of delivering a service, identity of hospital official, fairness in getting service, hospital amenities and service safety had the lowest mean score (NRR). Therefore, the study suggets the hospitals to improve its performance on those lowest five indicators especially its current queuing system because this is the most complaint from the patients.Keywords: BPJS Kesehatan patient, satisfaction index, service quality